Major trends in device to device communications research: A bibliometric analysis - Mukhlif, Fadhil; Hodonu-Wusu, James Oluwaseyi; Noordin, Kamarul Ariffin; Kasirun, Zarinah Mohd (2018)
The quantitative study of bibliographic material is referred to as bibliometric analysis. It presents a general overview of a research area where the published works can be classified based on countries, authors, publication years, keywords, and fields of research. This study aims to provide a bibliometric analysis of the research carried out in the field of device to device (D2D) communications in the past decade. The primary objective of this study is to find some of the most relevant and influential research papers in this field and define the newest trends as per the information available in the Web of Science database. During the course of this study, numerous classifications have been made based on different parameters such as the most productive and influential authors, and the most influential keywords and journals. The conclusions of this study are in line with the common wisdom, although certain deviations have been found.